Effect of the internal carotid artery degree of stenosis on wall and plaque distensibility - Loizou, Christos P.; Pantzaris, Marios C.; Kyriacou, Efthyvoulos C.; Nicolaides, Andrew N.; Pattichis, Constantinos S. (My University, 2021)
Carotid distensibility is an indicator of carotid elasticity, which can be used as a cardiovascular disease risk factor. The objective of this study was to investigate how the degree of stenosis influences the strain characteristics of wall and plaque in the internal carotid artery (ICA). Ultrasound videos of the ICA from 83 subjects with atherosclerotic plaques at the origin of the ICA producing variable degrees of stenosis from 10 % to 85 % were investigated. We estimate for each video a carotid diameter during contraction (CDC), a carotid diameter during distension (CDD) in mm and a % of carotid plaque distension (%CPD). We have also estimated the radial strain at wall and plaque (%RSw, %RSp), the longitudinal strain at wall (%LSw) and the shear strain at wall (%SSw) and plaque (%SSp) respectively. The main findings were the following: 1) The %CPD is linearly related to the percentage of ICA stenosis decreasing with an increase in stenosis. 2) There is a statistical significant difference between the % of ICA plaque distensibility of the AS group vs the SY group. 3) There is a statistical significant difference for the RSw, and LSw and %SSw of ICA wall of the AS group vs the SY group. 4) There is a statistical significant difference for the %SSp and %RSp between the AS group vs the SY group. The degree of the ICA stenosis is associated with strain metrics of the carotid wall and plaque. Future work will investigate the proposed methodology on more subjects.
Keywords: B-mode ultrasound; Degree of stenosis; M-mode; State-based identification; Strain measurements; Carotid artery